Characterization of Ralstonia strains infecting tomato plants in South Africa. (October 2018) - Shutt, V.M.; Shin, G.; van der Waals, J.E.; Goszczynska, T.; Coutinho, T.A.
Abstract: Ralstonia spp., the causal agents of bacterial wilt, cause severe yield losses of Solanaceous crops, including tomato. The disease is difficult to control due to the pathogen's ability to survive in soil and to cause latent infections. Therefore, characterizing Ralstonia strains is important in developing effective strategies for diagnoses, quarantine and selection of biocontrol agents. In this study, 50 Ralstonia strains previously isolated from wilted tomato plants in different locations in South Africa were obtained from the culture collection of the Agricultural Research Council, Pretoria, and private seed companies. A phylogenetic analysis of the endoglucanase gene sequences revealed that 49 strains were R. pseudosolanacearum and only one was R. solanacearum. R. pseudosolanacearum strains grouped into two sequevars, 18 and 31, while the single R. solanacearum strain grouped into the cold-adapted sequevar 1, also known as race 3 biovar 2. The pathogenicity results revealed that the selected strains were pathogenic on tomato seedlings. This study thus revealed that bacterial wilt of tomato is caused primarily by R. pseudosolanacearum, but R. solanacearum IIB-1 is also present in South Africa. This information is relevant in terms of the implementation of quarantine measures, notably to put into place measures that will prevent the introduction of strain IIB-1 into other provinces of South Africa. Highlights: The primary cause of bacterial wilt of tomato in South Africa is caused by Ralstonia pseudosolanacearum . A single strain of R. solanacearum was isolated and it grouped into the cold-adapted phylogroup IIB and sequevar 1. Two sequevars, viz. 18 and 31, are present in the R. pseudosolanacearum population.